Translation ideology in literary translation; A case study of Bram Stoker’s Dracula translation into Indonesian - Jaya, Doni (Wacana, Journal of the Humanities of Indonesia, 2020)
A literary text typically contains many cultural elements often presented in a very concise manner to enhance its readability and aesthetic quality. Its translation can be challenging when there is a gap between source culture and target culture. Thus, a translator has to make an ideological choice: either to foreignize or to domesticize. This paper aims to identify and examine the ideology applied by a literary translator when translating culturally-divergent translation units. Bram Stoker’s Dracula and its Indonesian translation by Suwarni were selected as data source due to the novel’s significant number of cultural references unfamiliar to modern Indonesians. Forty units were selected for this paper and classified into several groups. Results show that the translator used various strategies, both foreignizing and domesticizing ones, to translate even similar units, indicating her considerable freedom. Furthermore, the results also show that translation ideology is a flexible concept which can shift throughout a translation project and be represented as a multipoint continuum. Moreover, both foreignization and domestication may take place at different levels, depending on various factors such as presence of information, extent of modification, and relevance of information.